Association of Rab37 gene polymorphism and delayed menarche: a report of 2 060 women - YUAN Meng; YUAN Meng; CAI Yang; CAI Yang (陆军军医大学学报)
Objective‍　‍To explore the association between single nucleotide polymorphism (SNP) of Rab37 gene and the age at menarche(AAM). Methods‍　‍A case-control study design was used to conduct an epidemiologic survey on 2 060 women in a community in Jurong City, Jiangsu Province, and their venous blood samples were collected. ASA chip was used to explore the Rab37 gene genotyping of blood sample DNA to obtain the genotyping results for Rab37 SNPs rs62084865, rs10512597, rs35489971, rs1037170, rs6501732, rs77822106, and rs3178300. Based on menarche time of <16 years old or ≥16 years old, the participants were divided into 2 groups. Linear and logistic regression analyses were used to explore the association between the SNP of Rab37 gene and the age at menarche based on dominant, recessive and allelic models. Results‍　‍Among the 2 060 healthy women, 944 women had normal menstrual periods, while 1 116 women experienced delayed menarche. Linear regression analysis showed that the gene polymorphism of rs3178300 was negatively correlated with the age at menarche in females [recessive model: CC/CT+TT, β=-0.915, 95%CI(-1.692,-0.137), P=0.021; allelic model: T/C, β=-0.221, 95%CI(-0.410,-0.032), P=0.022]. Logistic regression analysis indicated that the gene polymorphism of rs3178300 was significantly associated with the risk of delayed menarche in females [recessive model: CC/CT+TT, OR=0.295, 95%CI (0.116,0.751), P=0.010; allelic model: T/C, OR=0.796, 95%CI(0.652,0.972), P=0.025]. The remaining 6 SNPs showed no significant association with age at menarche. Conclusion‍　‍The rs3178300 polymorphism of Rab37 gene is significantly associated with delayed menarche in Chinese women.